Circadian rhythm abnormalities of melatonin in Smith-Magenis syndrome. Issue 6 (1st June 2000) - Potocki, Lorraine; Glaze, Daniel; Tan, Dun-Xian; Park, Sung-Sup; Kashork, Catherine D; Shaffer, Lisa G; Reiter, Russel J; Lupski, James R
Abstract : BACKGROUND: Smith-Magenis syndrome (SMS) is a multiple congenital anomalies/mental retardation syndrome associated with a hemizygous deletion of chromosome 17, band p11.2. Characteristic features include neurobehavioural abnormalities such as aggressive and self-injurious behaviour and significant sleep disturbances. The majority of patients have a common deletion characterised at the molecular level. Physical mapping studies indicate that all patients with the common deletion are haploinsufficient for subunit 3 of the COP9 signalosome ( COPS3 ), which is conserved from plants to humans, and in the plant Arabidopis thaliana regulates gene transcription in response to light. Haploinsufficiency of this gene is hypothesised to be potentially involved in the sleep disturbances seen in these patients. Melatonin is a hormone secreted by the pineal gland. SMS patients are reported to have fewer sleep disturbances when given a night time dose of this sleep inducing hormone. METHODS: Urinary excretion of 6-sulphatoxymelatonin (aMT6s), the major hepatic metabolite of melatonin, in 19 SMS patients were measured in conjunction with 24 hour sleep studies in 28 SMS patients. Five of the 28 patients did not have the common SMS deletion. To investigate a potential correlation of COPS3 haploinsufficiency and disturbed melatonin excretion, we performed fluorescence in situ hybridisation (FISH) using two BACs containing coding exons of COPS3 . RESULTS: All SMS patients show significant sleep disturbances when assessed by objective criteria. Abnormalities in the circadian rhythm of aMT6s were observed in all but one SMS patient. Interestingly this patient did not have the common deletion. All patients studied, including the one patient with a normal melatonin rhythm, were haploinsufficient for COPS3 . CONCLUSIONS: Our data indicate a disturbed circadian rhythm in melatonin and document the disturbed sleep pattern in Smith-Magenis syndrome. Our findings suggest that the abnormalities in the circadian rhythm of melatonin and altered sleep patterns could be secondary to aberrations in the production, secretion, distribution, or metabolism of melatonin; however, a direct role for COPS3 could not be established.